Efektivitas Pelaksanaan Kebijakan Sistem Zonasi pada Penerimaan Peserta Didik Baru Tingkat Sekolah Menengah Pertama (SMP) Negeri di Kota Denpasar - I Kadek Dede Junaedy (Public Inspiration: Jurnal Administrasi Publik, 2022)
Implementation of Acceptance of New Students in Denpasar City in 2022 refers to Mayor Regulation Number 15 of 2022 concerning Guidelines for Admission of New Students in Kindergartens, Elementary Schools and Junior High Schools (Regional Gazette of Denpasar City Year 2022 Number 15), so that the capacity each school has been determined in accordance with the Mayoral Regulations of Denpasar City, including the capacity of State Junior High Schools (SMPN). The problem that occurred in the implementation of Student Admissions through the Zoning Path at the SMPN level, namely the emergence of tensions between the number of SD graduates and the capacity of SMPN in Denpasar City. The research method used in this study is to use the literature review research method. The results of this study are that the implementation of the zoning system policy at PDDB, especially at the state junior high school level in Denpasar City, has not been carried out effectively, due to the interest in the availability of schools in the city, the number of public elementary schools in Denpasar is 167, while there are 15 public junior high schools in Denpasar, and the uneven distribution adequate distribution of facilities and infrastructure.